2016
DOI: 10.1126/science.aaf2729
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of avian neural crest axial identity and cell fate

Abstract: Neural crest populations along the embryonic body axis differ in developmental potential and fate, such that only cranial neural crest can contribute to craniofacial skeleton in vivo. Here, we explore the regulatory program that imbues the cranial crest with its unique features. Using axial-level specific enhancers to isolate and perform genome-wide profiling of cranial versus trunk neural crest in chick embryos, we identify and characterize regulatory relationships between a set of cranial-specific transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 25 publications
3
122
0
Order By: Relevance
“…As for other lineages, we identified ELAVL4 and SMYD1 to be preferentially expressed in placode and NNE, respectively (Figure 4F). Furthermore, we compared our NC dataset to a previously published study focused on identifying NC in chick (Simoes-Costa and Bronner, 2016). Of the genes significant enriched in the NC, we found significant overlap (p-value: 3.56 × 10 −7 ) between the two datasets (reflecting key conserved NC markers (Figure S4C,D).…”
Section: Resultsmentioning
confidence: 99%
“…As for other lineages, we identified ELAVL4 and SMYD1 to be preferentially expressed in placode and NNE, respectively (Figure 4F). Furthermore, we compared our NC dataset to a previously published study focused on identifying NC in chick (Simoes-Costa and Bronner, 2016). Of the genes significant enriched in the NC, we found significant overlap (p-value: 3.56 × 10 −7 ) between the two datasets (reflecting key conserved NC markers (Figure S4C,D).…”
Section: Resultsmentioning
confidence: 99%
“…TFAP2b is essential for craniofacial development [18]. Sox10 is considered to be one of the earliest neural crest-patterning genes [19, 20]. In humans, TFAP2 is found highly expressed neural crest derived frontal compartment [21], and in chicken, Sox10 is the earliest neural crest-specifying gene [19], suggesting different neural crest specifiers may function in species-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the basic neural crest GRN was already present at the base of vertebrates, although some key regulators were missing from the lamprey neural crest specifier module 7 . Recently, our understanding of the composition and function of the neural crest GRN in gnathostomes has been greatly increased with the advent of next generation sequencing techniques including RNA-seq, ChIPseq and ATAC-seq [8][9][10][11][12][13][14][15] . Whereas the GRN of gnathostome neural crest has been greatly expanded, progress in reconstructing the neural crest GRN of jawless vertebrates has been limited due to incomplete genomic information.…”
Section: Introductionmentioning
confidence: 99%